PANDANGAN POLITIK JARINGAN ISLAM LIBERAL DI INDONESIA - Azmy, Ana Sabhana; Yusra, Amri (Academic Journal of Islamic Principles and Philosophy, 2020)
This article aims to look at the political views of the Jaringan Islam Liberal (Liberal Islam Network) in Indonesia. As a community that wants to carry out reforms with the spirit of modernization and rationality in religion, seeing it in political and democratic contestation in Indonesia is interesting. So this article questions two things; how does Jaringan Islam Liberal view the relevance of religion and politics? and how does Jaringan Islam Liberal view the implementation of democracy? The method used in this paper is a literature study that seeks to collect data from journal articles, books, and other related reading materials. This article shows that the Jaringan Islam Liberal (Liberal Islam Network) rejects forms of political Islam that try to formally fight for the superiority of Islamic value systems and symbols in the political sphere. They also reject the idea of an Islamic state and the formalization of shari'ah, and sees democracy as a value that must be implemented in a country. This is because it is in accordance with the basic rights that must be owned by individuals, which are known as human rights.